MiR-21 and mRNA PTEN Expression Levels and Biomarker Potential in Breast Cancer - Dinna Rakhmina; Sofia Mubarika Haryana; Teguh Aryandono (Medical Laboratory Technology Journal, 2021)
MiR-21 has been linked to tumorigenesis, development, and metastasis in tumor pathogenesis. All human cancers, including breast cancer, have increased expression of MiR-21, which is the only miRNA that has increased expression. PTEN expression was found to be reduced in the majority of solid tumors, including breast cancer. Since lymph node metastatic factors, estrogen receptor status, tumor grade, and tumor node metastasis (TNM) all decreased PTEN expression, the PTEN expression profile may be a very useful prognostic marker in breast cancer. PTEN inhibits PIP3 (phosphatidylinositol 3,4,5-triphosphate) activity by having protein phosphatase and lipid phosphatase activity that is the polar opposite of PI3K (Phosphatidyl Inositol 3-Kinase). The aim of this research was to see how often miR-21 and mRNA PTEN were expressed at different stages of breast cancer and whether they could be used as prognostic markers. This type of research is an observational study with a cross-sectional design. The sample size of 43 people came from breast cancer patients. Analysis of miR-21 expression and mRNA PTEN using Real-Time qPCR. The results showed that miR-21 expression increased 1.32 times at an advanced stage compared to an early stage, while mRNA PTEN expression decreased 1.33 fold at an advanced stage compared to an early stage. According to the findings, miR-21 expression in the blood plasma of breast cancer patients was upregulated at an advanced stage compared to an early stage and downregulated mRNA PTEN expression. MiR-21 which is increased at an advanced stage has the potential to be a poor prognostic marker at the stage of breast cancer. The change in miR-21 expression can be a good candidate as a molecular prognostic marker and for future research the role of miR-21 in breast cancer progression will further enrich the scientific repertoire, especially in the health and clinical fields.